Ameliorative and Synergic Effects of Derma-H, a New Herbal Formula, on Allergic Contact Dermatitis - Jo, Si Yeon; Kim, Mi Hye; Lee, Haesu; Lee, Sun Haeng; Yang, Woong Mo (Frontiers in Pharmacology, 2020)
Allergic contact dermatitis (ACD) is characterized by itching, skin inflammation and allergic responses caused by release of immunoglobulin E and T helper 2-specific cytokines. The aim of this study is to investigate the ameliorative and synergic effects of herbal formula, Derma-H, containing Astragalus membranaceus Fisch. ex Bunge (AM) and Nepeta tenuifolia Benth (NT) which have been used as traditional medicinal herbs for the cure of dryness, edema and pruritus. 2,4-Dinitrochlorobenzene (DNCB) was applied for ACD induction. AM, NT and a mixture of AM and NT was topically applied to skin lesions for 11 days. Dermatitis score and number of scratches were significantly diminished in AM, NT and AM + NT (Derma-H)-treated groups. Especially, Derma-H was more effective than single treatment of AM and NT on skin hyperplasia and mast cell infiltration. Also, NGF expression decreased by NT and a mixture of AM and NT. Additionally, series of TrkA, Raf-1, MEK and ERK were significantly inhibited by topical AM and NT application. Those findings suggested AM and NT treatment has a synergic effect on DNCB-induced ACD in mice.